FOUR-STATE CHUI-WEEKS MODEL ON THE CAYLEY TREE: TRANSLATION-INVARIANT GROUND STATES - Hakimova , Muslimaxon (THE PLACE AND ROLE OF TURKEY AND THE NEAR REGION IN THE PROCESSES OF SCIENTIFIC, SOCIAL, AND CULTURAL DEVELOPMENT, 2025)
The four-state Chui-Weeks model is studied on the Cayley tree of order two. All translation-invariant ground states of this model are completely classified.